Genotype, allele and haplotype frequencies of four TCL1A gene polymorphisms associated with musculoskeletal toxicity in the South Indian descent - Umamaheswaran, Gurusamy (Tabriz University of Medical Sciences, 2014)

(untitled)
Introduction: Decline in circulating estrogen levels causes lessening of bone mass accompanied with musculoskeletal pain, which is the primary cause of treatment discontinuation in patients taking aromatase inhibitors. Evidence from recent genome-wide association studies (GWAS) suggests that the genetic variability underlying TCL1A gene increases the risk of aromatase inhibitors (AIs) - induced musculoskeletal toxicity. Currently, no data is available on the frequency distribution of TCL1A gene polymorphisms in Indians. Methods: In this pilot study, we used TaqMan fluorescent probes to assess the genotypes of four TCL1A gene polymorphisms associated with musculoskeletal toxicity in 247 healthy homogenous South Indian subjects on real time thermocycler. Haplotype estimation and pairwise linkage disequilibrium (LD) analysis were executed by Haploview. Results: The incidence of polymorphic variant allele (G) frequencies of rs7158782, rs7159713, rs2369049 and rs11849538 were 22.1%, 23.5%, 18.2% and 22.9% in the study population, respectively. The polymorphisms were found to be in complete LD with each other. Four different haplotypes, each of which having a frequency of above 1% were inferred in South Indians using an expectation-maximization algorithm. Notably, three haplotypes were found to be population specific viz H4 A-A-A-G (1.2%) for South India, H5 G-G-A-C (1.3%) for JPT and H6 G-G-G-C (40.4%) for YRI. Further, H3 G-G-A-G (2.3-16.3%) haplotype occurs primarily in Asians and is virtually absent in Africans. Overall, the genetic variability and haplotype profile of South Indian population revealed significant inter-racial variability compared with HapMap data. Conclusion: This documentation contributes for further investigations on the pharmacogenetics of AIs in South Indians.